Desain dan Karakteristik Permukaan Kobalt Oksida pada Pendukung Katalis - Qurrota A'yuni (2477 - 6165, 2017)
Material surface characteristics are the main criteria to be considered in catalyst design. The surface area and catalyst porosity determine activity and selectivity in catalytic reactions. In this research, synthesis of cobalt oxide, calcium fluoride and calcium fluoride cobalt oxide has been done. Characterization of solid sufaces is analyzed by using Nitrogen Gas Adsorption Method. The surface area of solids is analyzed by using SBET and SBJH Methods. Identification of mesoporous both qualitative and quantitative is analyzed by using BJH Method. The result of synthetic solid shows the pattern of isotherm adsorption type IV which is typical for mesoporous material. Surface measurements show the presence of cobalt oxide on a catalyst support marked by decreasing surface area, pore size and pore volume of catalyst support material.